Renewable Energy Integration: Economic Assessment of Solar Energy to Produce Biodiesel at Supercritical Conditions - José A. León; Gisela Montero; Marcos A. Coronado; Conrado García; Héctor E. Campbell; José R. Ayala; Daniela Montes; Carlos A. Sagaste (International Journal of Photoenergy)
In recent years, research on noncatalytic methods for biodiesel production has increased, mainly processes under supercritical conditions that allow the processing of waste vegetable oils (WVO) without the need to use catalysts, where the absence of catalyst simplifies the processes of purification of biodiesel. The high consumption of alcohol and energy to maintain the appropriate conditions of pressure and temperature of the reaction has turned the processes of supercritical conditions into an unfeasible method. However, the stages of biodiesel purification and methanol recovery are more straightforward, allowing the reduction of the total energy consumption by 25% compared to alkaline methods. Therefore, the present work describes a study through Aspen Plus® of the production of biodiesel by a process in supercritical conditions with WVO as raw material. Also, a solar collector arrangement was structured using the TRNSYS® simulator to supply energy to the process. To evaluate the economic feasibility of the proposed process, the installation of a pilot plant in Mexicali, Baja California, was considered. The internal rate of return (IRR) and the net present value (NPV) were determined for ten-year period. The planned system allows supplying solar energy, 69.5% of the energy required by the process, thus reducing the burning of fossil fuels and the operation cost. Despite the additional investment cost, for the solar collectors, the process manages to maintain a competitive production cost of USD 0.778/l of biodiesel. With an IRR of 31.7%, the investment is recovered before the fifth year of operation. The integration and implementation of clean technologies are vital in the development of the biofuels.